Metal-containing Particulate Matter and Associated Reduced Olfactory Identification Ability in Children from an Area of High Atmospheric Exposure in Mexico City. (19th November 2019) - Guarneros, Marco; López-Rivera, Cristina; Gonsebatt, María Eugenia; Alcaraz-Zubeldia, Mireya; Hummel, Thomas; Schriever, Valentin A; Valdez, Bertha; Hudson, Robyn
Abstract: Air pollution has been linked to poor olfactory function in human adults. Among pollutants, particulate matter (PM) is especially relevant, as it may contain toxic metal ions that can reach the brain via olfactory pathways. Our purpose was to investigate the relation between atmospheric PM and olfactory identification performance in children. Using a validated method, we tested the olfactory identification performance of 120 children, 6–12 years old, from two locations in Mexico City: a focal group ( n = 60) from a region with high PM levels and a control group of equal size and similar socioeconomic level from a region with markedly lower PM concentrations. Groups were matched for age and sex. Concentrations of manganese and lead in the hair of participants were determined as biomarkers of exposure. Daily outdoor PM levels were obtained from official records, and indoor PM levels were measured in the children's classrooms. Official records confirmed higher levels of outdoor PM in the focal region during the days of testing. We also found higher classroom PM concentrations at the focal site. Children from the focal site had on average significantly lower olfactory identification scores than controls, and hair analysis showed significantly higher levels of manganese for the focal children but no difference in lead. Children appear to be vulnerable to the effects of air pollution on olfactory identification performance, and metal-containing particles likely play a role in this. Olfactory tests provide a sensitive, noninvasive means to assess central nervous function in populations facing poor air quality.